Avaliação de parâmetros globais de desempenho de biorreatores pneumáticos através de fluidodinâmica computacional - Rodriguez, Guilherme Youssef (Universidade Federal de São Carlos, 2015)
Pneumatic bioreactors are devices free of moving parts which have the purpose of converting raw materials in bio-products of commercial interest by the action of enzymes or cells. They are promising in the biochemical industry, ensuring good oxygen transfer and consuming less energy. Global performance parameters such as global gas hold up and the volumetric oxygen transfer coefficient are important criteria in the design and selection among different geometries of the mentioned devices. In the present work it was carried out modeling and simulation of pneumatic bioreactors based on Computational Fluid Dynamics (CFD) in order to estimate the global gas hold up and the volumetric oxygen transfer coefficient in three different geometries of pneumatic bioreactors: bubble column, concentric tube airlift and split tube airlift. The simulated results of each performance parameter were verified by comparison with the experimental values reported by Thomasi et al. (2010) and Mendes and Badino (2015) for the fluids distilled water, glycerol solution 10 cP and xanthan gum solution 0.2% w/v (weight/volume) in a wide range of specific air flow rate (0 to 5 min- 1). Application suite ANSYS® 14.5 was used for numerical simulations in CFD. Important parameters such as the bubble diameter played a great influence on results of the volumetric oxygen transfer coefficient. It can be observed by the experimental and simulated results that the concentric tube airlift bioreactor was the best alternative to the global gas hold up and the volumetric oxygen transfer coefficient (reaching 14% and 0.06 s-1 for distilled water, respectively). It was found that the results obtained via the CFD agreed with the majority trend of experimental data, capturing the most important hydrodynamic phenomena and mass transfer characteristics, showing that the modeling of different systems with different fluids fulfilled the main objective of obtaining reliable models design and performance of other geometries of pneumatic bioreactors.
Keywords: Biorreatores pneumáticos; CFD; Retenção gasosa; Pneumatic bioreactors; Global parameters; Gas hold up; Volumetric oxygen transfer coefficient; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA